The impact of food assistance on food insecure populations during conflict: Evidence from a quasi-experiment in Mali - Tranchant, Jean-Pierre; Gelli, Aulo; Bliznashka, Lilia; Diallo, Amadou Sekou; Sacko, Moussa; Assima, Amidou; Siegel, Emily H.; Aurino, Elisabetta; Masset, Edoardo (Elsevier, 2019)
Mali, a vast landlocked country at the heart of West Africa in the Sahel region, is one of the least developed and most food insecure countries in the world. Mali suffered from a series of political, constitutional and military crises since January 2012, including the loss of government control of northern territories from April 2012 until January 2013. A range of humanitarian aid interventions were scaled up in response to these complex crises. In this study, we exploit data from a unique pre-crisis baseline to evaluate the impact of humanitarian aid on the food security of rural populations.